Antioxidants - Benefits, Sources, Mechanisms of Action 2021
DOI: 10.5772/intechopen.95791
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Infertility

Abstract: Unexplained sub-fertility is commonly identified if couples fail to conceive after 1 yr. of everyday unprotected sexual intercourse even though investigations for ovulation, tubal patency and semen evaluation are ordinary. Many previous studies had shown that oxidative stress plays an important role in human fertility. Free radicals are neutralized by an elaborate antioxidant defense system. In a healthy body, pro-oxidants and antioxidants maintain a ratio and a shift in this ratio towards pro-oxidants gives r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…A deeper comprehension of these enzymes' roles could elucidate the pathomechanisms of various reproductive ailments and potentially pave the way for innovative therapeutic interventions. 44 Non-enzymatic antioxidants The female reproductive system consists of specialized organs and functions designed to support conception, pregnancy, and childbirth. This system can be affected by OS from environmental sources, natural bodily reactions, or metabolic waste products.…”
Section: Glutathione Peroxidase (Gpx)mentioning
confidence: 99%
“…A deeper comprehension of these enzymes' roles could elucidate the pathomechanisms of various reproductive ailments and potentially pave the way for innovative therapeutic interventions. 44 Non-enzymatic antioxidants The female reproductive system consists of specialized organs and functions designed to support conception, pregnancy, and childbirth. This system can be affected by OS from environmental sources, natural bodily reactions, or metabolic waste products.…”
Section: Glutathione Peroxidase (Gpx)mentioning
confidence: 99%
“…Many previous studies had shown that oxidative stress plays an important role in human fertility. Elevated concentrations of reactive oxygen species (ROS) may have detrimental effects on the spermatozoa, oocytes, sperm oocyte interaction and embryos both in the Fallopian tube and the peritoneal cavity leading to infertility (Mahmood et al, 2021). "Female corrective" is a poly-herbal medicine formulation that is used in the southeastern part of Nigeria for the treatment of women infertility.…”
Section: Introductionmentioning
confidence: 99%